PENDAMPINGAN ORANG TUA TERHADAP PERKEMBANGAN ANAK DALAM MENONTON TAYANGAN TELEVISI GUNA MENUMBUHKEMBANGKAN MINAT BACA - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The purpose of the study is to describe the role of parental companions in watching television to develop children’s reading interest. The study is an object of discussion that focuses on analysis based on studies that have a comprehensive, detailed nature of important and main content, namely; the role of parental assistance in watching television for the development of children’s reading interest. The study covers a basic analysis, based on the focus of the main study on the role of parents in managing the development of children’s reading interest through television viewing assistance. Analysis requires critical thinking of reality, in order to carry out the application of conceptualization to historical developments in the past or is happening, using a historical approach, characterized by a realistic investigation of the development of a thought. Primary information sources function as the main elements of primary data. The historical approach data collection technique makes optimal use of the research library by reading the related literature; family function, the role of parents, interest in reading, television programs and their impact. Qualitative descriptive analysis is used based on sources of analysis based on various kinds of reading materials that are theoretical, research and not research. To achieve the validity of the study requires efforts to utilize content analysis to analyze the meaning of the various conceptualizations that are the main study. Observations were made to see the role of parents, the function of the family, used as elements of theory construction, especially the meaning of family functions, the role of parental companions, the growth of interest in reading, as well as watching television shows. The results showed that; (1). The role of parents is very important and plays a strategic position in the development of children, so as not to fall into something negative. (2). The role of parents in watching television is very urgent for parents to do, because it functions to supervise, direct and guide children to develop reading interest.